Numerical modelling for rain wind induced vibration of cables with longitudinal ribs. Issue 178 (July 2018) - Bi, J.H.; Qiao, H.Y.; Nikitas, N.; Guan, J.; Wang, J.; Lu, P.
Abstract: Aerodynamic countermeasures are among the most effective ways to mitigate rain-wind induced vibrations. However, their vibration control mechanism is in many cases still unclear. This paper presents a numerical model for a cable section with an arbitrary 2D shape, able to geometrically describe aerodynamic countermeasures, excited by both wind and rain. Based on lubrication and vibration theory, 2D coupled equations for the water film evolution and for the across wind cable vibration are derived. Wind pressure and friction coefficients, for the different evolving water-film morphologies, are calculated by CFD software, while the instantaneous water film distribution and the vibration of the cable are calculated by numerically solving the derived coupled equations. For the case of rib additions to a nominally circular cable, the model shows that there is direct impact on the formation and dynamic characteristics of the critical for rain-wind induced vibrations upper rivulet. Particularly, depending on the rib number and position(s), the countermeasure can become effective or not by altering the lift acting upon the cable, and redistributing its frequency content associated with instability phenomena. Highlights: A new numerical model is presented to describe cable with an arbitrary 2D shape under wind and rain. Coupled equations of water film evolution and cable vibration are derived. The case of cable with ribs are investigated by solving the coupled equations. The vibration characteristics of cable, rivulets and lift are investigated to analyze a possible mitigation mechanism.